Unlocking the Potential of Blockchain for Health Data Security: A Narrative Review - Mayasari, Dina (Medicor : Journal of Health Informatics and Health Policy, 2024)
The rapid digitization of healthcare has intensified concerns about data security, patient privacy, and system interoperability. This narrative review critically examines the potential and challenges of blockchain technology in addressing these issues. A systematic search was conducted in Scopus, PubMed, IEEE Xplore, and Google Scholar, focusing on studies published between 2019 and 2025 that explored blockchain applications in healthcare data security. The evidence indicates that blockchain provides tamper-proof storage of electronic health records, strengthens patient control through permissioned access, and enables transparent audit trails. Compared to conventional technologies, blockchain demonstrates stronger resilience against cyberattacks and enhances interoperability across fragmented systems. Integration with Artificial Intelligence and the Internet of Things further improves real-time analytics and secure device communication. However, barriers such as scalability constraints, high costs, regulatory uncertainty, and limited institutional expertise hinder its widespread adoption. These challenges are particularly acute in low- and middle-income countries with limited infrastructure. The findings highlight the need for supportive policies, sustainable funding, and workforce training to enable equitable implementation. This review contributes by synthesizing current evidence, clarifying systemic barriers, and outlining strategies for responsible blockchain integration in healthcare systems.